Perceived difficulty of numbers relates to self-reported achievement in adults - Sunde, Pernille; Pind, Pernille; Sunde, Peter (MONA - Matematik- og Naturfagsdidaktik, 2024)
Are some numbers perceived as more difficult than others, and if so, is this dependent on general mathematical ability? We analysed 689 adults’ (age >18 years) responses to a questionnaire on perceived difficulty of and preference for different numbers’ multiplications. Participants with low self-reported mathematical ability score (MAS) perceived difficult numbers, i.e., numbers including digits 7 and 8, as more difficult than high MAS participants did. This has implications for teaching as well as for research. If a task is perceived as difficult due to the presence of specific digits, this could influence performance and ability to engage in, for example, learning activities.